Formation and breakup patterns of falling droplet - Sharafatmandjoor, Shervin (Taylor and Francis Inc., 2015)
Some interface front patterns of falling droplets are studied via direct numerical solution of the full Navier-Stokes equations governing the system of droplets and the ambient surrounding media as a single-fluid model. We focus on the mutual interactions of the effects of characterizing nondimensional parameters on the formation and break-up of large cylindrical droplets. The investigation of droplet cross sections and deformation angles shows that for moderate values of the Atwood number, increasing the Eötvös number explicitly increases the deformation rate in formation and breakup phenomena. Otherwise, increasing the Ohnesorge number basically amplifies the viscous effects